Reimagining a Lost Armenian Home: The Dildilian Photography Collection - Marsoobian, Armen (I.B. Tauris, 2017)
For nearly a century members of the Dildilian family practiced the art of photography in Ottoman Turkey, Greece and the United States. This book contains over 200 photographs, primarily from the Ottoman era, beginning with the creation of the family business by Tsolag Dildilian in Sivas in central Turkey in 1882 and concluding in 1922 in Samsun, when the family was forced into exile in Greece. The photographs and the stories that unfold around them capture a defining period in the nearly three thousand year history of the Armenians in Anatolia and the Armenian Highlands. The early-twentieth century witnessed the violent erasure of the Armenians from their historic homeland, with catastrophic effects for the Dildilian family and their community. Yet this was also a period of unprecedented educational, cultural and commercial development for the Armenians. The Dildilian family was intimately involved in the triumphs and tragedies of these years and this book, through its rich pictorial history, sheds unprecedented light on the real-life experiences of Armenians in the devastating years of the Armenian Genocide and beyond. It is an unusual and original contribution to the social history of the Near East.
Keywords: Dildilian family; Armenians; Pictorial works; Portraits; Armenia; dept.phi; faculty_collection

The Armenian genocide in film: overcoming denial and loss - Marsoobian, Armen T (The history of genocide in cinema: atrocities on screen, 2017)
Keywords: dept.phi